PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMEN UNTUK MENINGKATKAN TANGGUNG JAWAB DAN PRESTASI BELAJAR SISWA - Poniyem (UNIB Press, 2024)
The aims of this research are to: 1). Describes the application of the cooperative learning model of the type of team games tournament to increase student responsibility in the fourth grade Mathematics lesson at SD Negeri 06 Teras Terunjam.2). Describes the application of the cooperative learning model of the type of team games tournament to improve student achievement in the fourth grade Mathematics lesson at SD Negeri 06 Teras Terunjam. 3). Describe the effectiveness of the application of the cooperative learning model of the type of team games tournament to increase the responsibility and learning achievement of students in the fourth grade Mathematics subject at SD Negeri 06 Teras Terunjam. In this study, the Classroom Action Research (CAR) method was used and continued with experimental research. The subjects of this research were fourth grade students of SDN 06 Teras Terunjam. Data collection techniques used in the study were observation sheets and student test methods. Analysis of the data used values ​​are (1) Analysis of Responsibility, (2) Analysis of Pre-test and Post-test, (3) Analysis of the t test of Student Achievement. The material validation instrument and student responsibility in the research used was the Linkert scale model. The conclusions of this research are; (1) The application of TGT type cooperative learning can increase students' responsibility in Mathematics. (2) The application of the TGT type of cooperative learning model can improve student achievement in Mathematics at SDN 06 Teras Terunjam in the 2022/2023 academic year and (3) The application of the TGT type of cooperative learning model is effective in improving student achievement compared to conventional learning models